2020
DOI: 10.3390/info11030127
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Mobile Augmented Reality Platform with Game-Based Learning Purposes

Abstract: Augmented reality (AR) is an emergent technology that overlays virtual objects into the real environment. Lately, AR is gaining prominence in education because of its increasing affordability through computers or mobile technologies. In addition, research sustaining the benefits of AR to promote student’s engagement to learn is increasing every day. However, the literature identifies lack of studies about the use of AR in education, namely, studies focused on the development of AR games designed over specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…Several surveys including questionnaires were conducted with primary school students and teachers. According to the results, the application enhances the students' interest to learn about solar system and keep them engaged [29].…”
Section: Literature Reviewmentioning
confidence: 98%
See 4 more Smart Citations
“…Several surveys including questionnaires were conducted with primary school students and teachers. According to the results, the application enhances the students' interest to learn about solar system and keep them engaged [29].…”
Section: Literature Reviewmentioning
confidence: 98%
“…The authors concluded proposed system improved students learning motivation [28]. • Maria Cristina Costa et al presented a mobile augmented reality based application called PlanetarySys-temGo which is a location-based game to promote learning about the universe [29]. The architecture of the system is divided into three components: platform server (manages all data in the system), Web application (the assessment of learning outcomes with a back office) and mobile app (created using unity 3D to provide dynamic environment to create AR content) as shown in Fig.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations